Testudo graeca tripolitania, a new taxon of spur-thighed tortoise found in Libya at risk of exploitation for the international pet trade - Poterala, Stephen F.; Rattay, Paul; Johnson, Aaron S.; Buijlayyil, Murad S. A.; Kiraz, Askin; Ajaj, Ahmad M. S. (Basic & applied herpetology, 2024)
The spur-thighed tortoise, Testudo graeca, is a widely distributed and deeply diversified species inhabiting areas of Africa, Asia, and Europe. For decades, populations of T. graeca from North Africa have been exploited for the international pet market. In particular, T. graeca of Libyan origin have been commercially imported into the United States several times since 2021. Using mitochondrial DNA (mtDNA) sequencing, we show that these imported tortoises include T. g. cyrenaica and a novel lineage originally reported in 2017 from a displaced specimen from a market in Libya. That novel lineage inhabits northwestern Libya, and we show that wild populations near Gharyan share the same mtDNA haplotype as those now sold as pets in the USA. Populations of T. graeca in northwestern Libya, previously identified as T. g. nabeulensis, are reassigned to a new subspecies Testudo graeca tripolitania described herein. Additional field work is needed to determine the mtDNA haplotypes of populations in central and southern Tunisia and to locate the subspecies boundary between T. g. nabeulensis and T. g. tripolitania.